Zagadnienia etyczne w procesach przekształceń własnościowych Województwa Łódzkiego - Barańska, Danuta; Michalak, Marek Jacek (Annales. Etyka w Życiu Gospodarczym, 2008)
The Polish society has perceived privatization as an issue of special importance which enables a free market economy in a short time. Privatization has always raised hopes and expectations. It is the lack of experience in the field of ownership transformations, the level of their complexity and the economic, legal, psychological and other conditionings that have confronted those transformations with many hindrances. They have also raised numerous moral and ethical dilemmas among the staff of privatized companies and founding organs including the staff of the Voivodship Council of Łódź. The decisions of the Working Board of one company about the future path of privatization have raised concerns among the staff uncertain of the fate of their place of work. In such cases the voice of the staff, which previously contributed to the company’s financial status, has always been decisive when choosing the path of privatization; this concerns mostly workers’ partnerships. It was John Paul II’s words about people of conscience who are needed in Poland, which were said in Skoczów, that were crucial for privatization decisions by the Voivodship Council of Łódź.